EFEKTIVITAS PEMBERIAN REBUSAN DAUN SALAM TERHADAP NYERI DISMENORE - Nadia Sari; Abqariah; Wahidanur (Sagita Academia Journal, 2024)
Dysmenorrhea is a problem for women because it can interfere with daily activities. Management of dysmenorrhea can be handled both pharmacologically and non-pharmacologically. Non-pharmacological treatment of dysmenorrhea includes other position settings, relaxation techniques, touch management, environmental management, distraction, behavioral support, imagination, compression. and giving herbal concoctions. One of the plant ingredients that can be used to treat dysmenorrhea is bay leaf decoction which aims to reduce pain during menstruation. This study aims to determine the effectiveness of giving bay leaf decoction in reducing dysmenorrhea pain in female students at SMP Negeri 1 Simpang Tiga, Pidie Regency. This research is an analytical survey using the Quasy Experiment method with a simple random sampling design. The sample in this study was 32 respondents. The sample size for the experimental group was 16 people and the sample size for the control group was 16 people. The results of the univariate test showed that the level of dysmenorrhea pain before administering the bay leaf decoction was mostly at a level of more than 7 respondents (43.8%), and the level of dysmenorrhea pain after administering the bay leaf decoction was mostly at a painless level of 13 respondents (81.2%). ) . The results of the bivariate test obtained a p value of 0.000 (p value <0.05), this shows that giving bay leaf decoction for dysmenorrhea has proven to be effective. Bay leaves have many health benefits, including diabetes, ulcers, stroke and blocked blood vessels. The mineral content in bay leaf decoction improves blood circulation so it can reduce menstrual pain.